Give-a-Damn Jones - Pronzini, Bill (Forge, 2018)
Give-a-Damn Jones arrives in a small Montana town rife with tensions related to a convict's efforts to prove his innocence, a cattleman's demand for respect, a snooping editor, and a feud between a dentist and a blacksmith.